2018
DOI: 10.1016/j.jid.2017.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte-Specific Ablation of RIPK4 Allows Epidermal Cornification but Impairs Skin Barrier Formation

Abstract: In humans, receptor-interacting protein kinase 4 (RIPK4) mutations can lead to the autosomal recessive Bartsocas-Papas and popliteal pterygium syndromes, which are characterized by severe skin defects, pterygia, as well as clefting. We show here that the epithelial fusions observed in RIPK4 full knockout (KO) mice are E-cadherin dependent, as keratinocyte-specific deletion of E-cadherin in RIPK4 full KO mice rescued the tail-to-body fusion and fusion of oral epithelia. To elucidate RIPK4 function in epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…However, the mechanism by which the stem cell membrane interacts in this process still needs to be further explored. The tight junction and LC layer, as the two main barriers of transdermal delivery, are believed to interact with each other and alter lipid organization [33]. Based on our findings, we hypothesize that the LC layer, tight junction, and endocytosis all play an important part in the mechanism of transdermal delivery and can interact with each other (Fig.…”
Section: Altered Expression Of Endocytosis-related Proteinsmentioning
confidence: 53%
“…However, the mechanism by which the stem cell membrane interacts in this process still needs to be further explored. The tight junction and LC layer, as the two main barriers of transdermal delivery, are believed to interact with each other and alter lipid organization [33]. Based on our findings, we hypothesize that the LC layer, tight junction, and endocytosis all play an important part in the mechanism of transdermal delivery and can interact with each other (Fig.…”
Section: Altered Expression Of Endocytosis-related Proteinsmentioning
confidence: 53%
“…However, the mechanism by which the stem cell membrane interacts in this process still needs to be further explored. The tight junction and LC layer, as the two main barriers of transdermal delivery, are believed to interact with each other and alter lipid organization [36]. Based on our ndings, we hypothesize that the LC layer, tight junction, and endocytosis all play an important part in the mechanism of transdermal delivery and can interact with each other (Figure 9).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have indicated that RIPK4 can modulate the actin cytoskeleton and restrict intercellular adhesion (6). Skin-specific loss of RIPK4 results in delayed keratinization, stratum corneum maturation, and aberrantly lipid distribution (7). Therefore, RIPK4 is essential for keratinocyte differentiation and the formation of a normal epidermal barrier (6).…”
Section: Introductionmentioning
confidence: 99%